Electrocatalytic nitrogen reduction directed through the p-band center of boron on BSAC@Mo2C - Maibam, Ashakiran; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Materials Advances, 2021)
Greener modes of ammonia synthesis via the electrocatalytic route have been investigated on pristine and defective Mo2C based monolayers anchored with metal-free boron atom catalysts. Boron single atom catalysts (SACs) on the defective Mo2C monolayer has been found to activate N2 strongly with an adsorption energy of −1.92 eV and reduce it to NH3 efficiently with a significantly low overpotential of 0.41 eV. The exothermic adsorption of N2 and low overpotential for the nitrogen reduction reduction (NRR) appertain to the p-band center of the boron atom catalyst and charge transfer between the adsorbed N2 and the catalyst, respectively. This work brings forth the correlation between electron occupancy on the boron center and NRR catalytic efficiency on a metal-free SACs@Mo2C monolayer couple, thereby serving as a lead in designing metal free electrocatalysts for the NRR.

Enhanced photocatalytic properties of a chemically modified blue phosphorene - Maibam, Ashakiran; Das, Sawan Kumar; Samal, Pragnya Paramita; Krishnamurty, Sailaja (RSC Advances, 2021)
It is high time to placate the peak demand for an efficient, economic and green fuel in the form of H-2 through photocatalytic water splitting. Several low dimensional materials have been explored for their photocatalytic properties on account of their surface to volume ratio. The present study illustrates the excellent photocatalytic potential of a two-dimensional material, viz. a chemically tempered blue-phosphorene sheet, with single atom thickness and high carrier mobility. Metal-free element, sulphur, is explored as a dopant in a 32-atom blue-phosphorene sheet. The dopant is inserted at three locations viz. central, edge and central edge positions with varying concentrations from 3.125% to 18.75% (corresponding to n = 1 to 6 sulphur atoms within a 32-atom blue-phosphorene sheet, P32-nSn). The cohesive energy studies predict the higher stability of even number S doped sheets as compared to their odd counterparts. Photocatalytic activity is studied in terms of band gap and band alignment for different concentrations of the former. Studies reveal that edge doping demonstrates better water molecule activation independent of S atom concentration. The edge doped systems not only provide the chemical activity to activate water, but also show feasible HER overpotentials of 1.24-1.29 eV at neutral medium. Finally, this work opens up a driving lead of non-corrosive catalysts for water molecule splitting.

Exploring edge functionalised blue phosphorene nanoribbons as novel photocatalysts for water splitting - Maibam, Ashakiran; Chakraborty, Debalina; Joshi, Krati; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Hydrogen gas, a highly combustible and eco-friendly fuel is stealing the limelight and its production is one of the major areas of research. An efficient and green method for producing clean hydrogen gas with no harmful by-product is water splitting. With the introduction of low dimensional materials, water splitting has become an easier and cost-effective process. The present work demonstrates the application of one such low dimensional material viz., edge functionalised Blue Phosphorene Nano-Ribbons (BPNRs) as potential photocatalysts. With a carrier mobility of 10(3) cm(2) V-1 s(-1) and a band gap of 1.5-3.0 eV, BPNRs are an attractive candidate for photocatalysis. BPNRs with different edge oreintations, viz. zigzag and armchair are functionalised with CH3O, COOCH3, CHO, COOH, OH, NH2, CONH2, SH, C6H5, and NO2 groups. Their performance towards activating water molecules at different sites on the nanoribbon is studied. The functionalised edges of the BPNRs are the active sites showing similar to 1.2% to 3.2% efficiency in activating the O-H bond of the water molecule. Among the different groups explored, CONH2 functionalised zigzag BPNR clearly exhibits a higher potential towards the adsorption of water molecules (-0.98 eV) and activation of O-H bonds with an elongation of 3.2% and a red shift of 500.6 cm(-1). This is attributed to the lone pair of electrons on the nitrogen atom contributing to the electron donating nature of the CONH2 functional group.

Electrocatalytic nitrogen reduction on defective graphene modulated from single atom catalyst to aluminium clusters - Maibam, Ashakiran; Krishnamurty, Sailaja; BabaRao, Ravichandar (Applied Surface Science, 2023)
Density Functional Theory (DFT) investigation on the most earth-abundant Al-based catalysts, has been conducted detailing its electronic properties and catalytic efficacy for nitrogen reduction at ambient condition. The Al-based catalysts have been modulated to perform as par a highly performing, but rare, Ru-single atom catalytic center by varying number of Al atoms, shape, and size. The coalesce of band-center, work function and electronic properties in metal atom catalysts along with N-N bond activation has been demonstrated to be responsible for an efficient nitrogen reduction reaction (NRR) with Delta Gmax of 0.78 eV in Al5 supported on N-doped double vacancy graphene (Al5@N4-DVG) catalyst. Electron localization function analysis has shown a weak physisorption of N2 in the Al-based catalysts. Projected Density of States (PDOS) illustrates the enhancement of aluminium electron density in Al5@N4-DVG led to enhanced orbital densities overlap of Alp and Np electrons. The Bader charge analysis and electronic analysis of the intermediates show efficient electron gain on the N atoms, leading to formation of NH3 from the NxHy intermediates in Al5@N4-DVG catalyst.